Comparative Analysis of Supreme Court and State Administrative Court Decisions in Land Disputes of Former Building Use Rights Certificates(Case Study of Suroto in Semarang) - Opi Winarti (Faculty of Law, Universitas Negeri Semarang, 2025)
Land disputes are a legal problem that often occurs in Indonesia and require legal certainty in their resolution. One example of a case regarding land ownership issues is in Decision Number 2341 K/Pdt/2016 and Number 50/G/2021/PTUN.SMG. The Suroto case is one example of the difference in decisions between the Supreme Court and the State Administrative Court in determining the validity of land title certificates. This difference has an impact on the protection of ownership rights and legal certainty for the community. This study aims to determine and analyze the comparison of the decisions of the Supreme Court and the State Administrative Court in resolving land disputes, especially in the Suroto case. In addition, this study also examines the legal implications of the differences in these decisions on legal certainty in resolving land disputes. The research method used in this study is normative juridical with a qualitative approach. The results of the study show that: (1) The Supreme Court considers the substantive aspect that the legal aspect of ownership must be based on the previously issued document, as long as there is no element of legal defect in the issuance process, while the PTUN in this decision emphasizes the procedural and administrative aspects related to the legality of the KTUN; (2) The impact of the differences in the decisions of the Supreme Court and PTUN is legal uncertainty for the Plaintiff, where the legality of the previously issued certificate is defeated due to the administrative procedures of the KTUN. Therefore, there needs to be clearer synchronization of laws and policies in resolving land disputes between the Supreme Court and PTUN in order to create legal justice for the community.